Detecting the Spatial Mismatch of Water Resources and Grain Planting Pattern Changes in China Based on Satellite Data - Feng, Yinan; Wang, Jieyong (Frontiers in Environmental Science, 2022)
China has achieved sustained growth in grain production and significant changes in grain patterns since the early 21st century. Meanwhile, the contradiction between the shortage of water resources and the development of agriculture is becoming more and more severe. This study introduced Gravity Recovery and Climate Experiment (GRACE) gravity satellite Total Water Storage (TWS) Product to indicate total water storage and calculated the Cumulated Normalized Difference Vegetation Index (CNDVI) of cropland as an indicator for grain growth. Based on the continuous satellite data, this paper revealed the spatial mismatch between water resources supply and grain growth pattern in China. The center of gravity of the CNDVI tends to move northwest, while the GRACE TWS data's center of gravity is in the opposite direction. There were different relationships between GRACE-TWS and CNDVI changes in different zones. We calculated the pixel-wise spatial Pearson Correlation coefficients of TWS and CNDVI. The TWS data and CNDVI data show negative correlation trends in the water-limited areas such as the northern arid-semiarid region and northern China plain, while they show a positive correlation in relatively sufficient water resources in southeast China. According to the results, the changing pattern of grain production in China is likely to cause the depletion of grain production potential in the water-limited regions, while the southeastern regions with higher potential still have more capacity for agricultural production.